Training Programmes and Success of Agri Clinics and Agri Business Centres (Acabcs) In Karnataka – An Evaluation - G, MR. SANDEEPA; SARALA, DR. K. S. (The journal of contemporary issues in business and government, 2021)
Agriculture Sector is contributing 16.5%to the GDP of the country and has enclosed more than 50% workforce are still engaged in agriculture and allied activities. (Economic survey 2019-20)Though higher workforce is involved, they are not self-reliable to earn their livelihood and it is indispensable to rethink the shift of agricultural sector. In this scenario Agri entrepreneurship or farm entrepreneurship apparently benefits the small-scale farmers to be self- reliable and independent. The National Institute for Management of Agricultural Extension (MANAGE) has classified 32 activities of agribusiness all over India (as on 5th February 2021) covering horticulture, floriculture, sericulture, dairy farming, poultry, agri clinics and agribusiness centres. Agri Clinics and Agri Business Centres (ACABCS) in the post globalization era have emerged as an important commercial activity in agriculture and Agribusiness undertakings formed by trained agriculturists. Such business may include sale of inputs, maintenance and custom hiring of farm equipment with other facilities in agriculture and allied areas as well as market linkages for revenue generation, post-harvest administration and entrepreneurial progress. Nodal Training institutes are contributing significantly for the development and growth of ACABCs. With this background, the study is undertaken at with an objective of examining the relationship of training programmes and the success of ACABCs in Karnataka. Sixty (29 Trained and 31 untrained) sample Agripreneurs drawn from Bengaluru urban and rural districtswere contacted with a structured questionnaire to understand their business growth and success level with the help of various parameters. Hypothesis testing was done with the help of Chi square test. For analysis simple percentage technique was applied. It has also come out with few findings and suggestions.